Impact of Nisin on Proliferation of Background Microbiota, Pressure-Stressed and Wild-Type Listeria monocytogenes, and Listeria innocua During a Real-Time Shelf-Life Study - Ranju Kafle; Aliyar Cyrus Fouladkhah (Microorganisms)
With the rapid implementation of high-pressure processing in many sectors of the food industry, considerations associated with pressure-stressed microorganisms are emerging. Nisin was utilized in this study for controlling the proliferation of Listeria monocytogenes and L. innocua inoculated on cold-smoked trout during a 4-week refrigerated shelf-life trial. Wild-type and pressure-stressed phenotypes of Listeria were compared in this study. The pressure-stressed phenotypes were prepared by treating the surrogate strain and pathogen mixture at 103.4 MPa (15K PSI) for 20 min. L. monocytogenes multiplied extensively during the 4-week refrigerated trial and counts were increased (p < 0.05) from 3.68 ± 0.1 log CFU/g on the first week to 6.03 ± 0.1 log CFU/g. Both phenotypes and the surrogate microorganisms illustrated similar (p ≥ 0.05) multiplication trends. Unlike samples subjected to water treatment, nisin was effective (p < 0.05) in keeping the microbial counts lower compared with the controls, particularly earlier during the shelf-life trial. Our study illustrates that the selected surrogate microorganism has comparable sensitivity to nisin relative to L. monocytogenes and thus could be used interchangeably in future public health microbiology challenge studies with similar scope. Additionally, we observed that pressure-stressed L. monocytogenes has proliferation and sensitivity to nisin comparable to wild-type pathogen.